Design and fabrication of a novel millimeter-wave bandstop filter using transversal signal interference technique - Salaheddine Barou; Jamal Zbitou; Stéphane Ginestar; Mohammed El Gibari (Institute of Advanced Engineering and Science, 2026)
This paper presents the design, simulation, and fabrication of a miniaturized millimeter-wave band-stop filter (BSF) on microstrip technology. The proposed arrangement is based on the concept of transversal interference of signals, and is realized as a pair of parallel transmission lines with the appropriate characteristic impedance and electrical length. Such scheme provides sharpening signal discrimination without resonator structures additional to the filter. The filter is fabricated on a ROGERS RT/Duroid 5880 substrate, selected for its favorable properties at high frequencies, including a thickness of 0.13 mm, a relative dielectric constant of 2.2, and a loss tangent of 0.0009. The optimized design was validated through electromagnetic simulations by two types of electromagnetic solvers, and then fabricated and measured by coplanar waveguide (CPW) probe to confirm its practical performance.